The rise of the novel - Seager, Nicholas; Tredell, Nicolas (Houndmills, Basingstoke, Hampshire Palgrave Macmillan, 2012)
This guide explores the dominant methodologies, theories and debates surrounding the emergence of the novel during the 18th-century. Covering key criticism on authors such as Defoe, Fielding, Richardson and Austen, the emphasis is on how critical work is interrelated, allowing readers to discern trends in the critical conversation.
Includes bibliographical references (pages 203-215) and index.
Keywords: English fiction -- 18th century -- History and criticism